Real-time remote monitoring system for crop water requirement information - Wenting, Han; Zhiping, Xu; Yang, Zhang; Pei, Cao; Xiangwei, Chen; Ooi, Su Ki (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Rapidly acquiring and real-time transmitting crop water requirement information constitute the basis for achieving intelligent diagnosis and precision irrigation. In order to collect and transmit crop water requirement information at real time, a new microcontroller-based real-time remote monitoring system was designed, including system hardware design, software and anti-jamming design. The system achieved the functions including clock reading, information configuration, LCD display, keyboard control, data sending and receiving, multi-channel information acquisition, conversion and storage. Laboratory and field tests showed that the system can achieve data acquisition and real-time display of the crop water requirement information. Unlike the current weather station, the system collects crop water information, meteorological factors and soil parameters at the same time. It has a high level of stability and acquisition accuracy, and can meet the requirements for real-time remote monitoring of the crop water requirement information for irrigation decision-making. Keywords: crop water requirement, information collection, microcontroller, real time monitoring, irrigation decision making DOI: 10.3965/j.ijabe.20140706.006 Citation: Han W T, Xu Z Q, Zhang Y, Cao P, Chen X W, Ooi S K. Real-time remote monitoring system for crop water requirement information. Int J Agric & Biol Eng, 2014; 7(6): 37－46.